STUDI RELEVANSI MODEL PEMBELAJARAN YANG DIGUNAKAN GURU DENGAN KOMPETENSI DASAR PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Bayu Yoga Prasetya; Machmud Al Rasyid; Wijianto Wijianto (PKn Progresif : Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2019)
The aims of this study are: 1) Describe the learning models used by the teachers on Citizenship Education subject. 2) Explain the relevance of the learning models used with the basic competencies in Citizenship Education subject. According to the results of the study, there are two conclusions. The first one is the teachers use a few learning models in Citizenship Education. The first model is the class based-passive cognitive pedagogies model. The teacher has planned the subject as stated in the lesson plan (RPP). This model emphasizes traditional learning about how the teacher provides initial definitions, principles, and concepts of learning materials and provides examples of problem-solving exercises in the form of lectures, demonstrations, question and answer, and assignments. The second model is the application of the model used by the teacher, namely lectures. The second conclusion is, the learning model used by the teachers in Wikarya Vocational School is not yet relevant to the basic competencies in the school. This can be seen from a number of facts, namely: a) the plan for implementing learning that has been prepared by the teacher does not fully reflect the circumstances during the learning process. b) The teachers do not apply everything contained in the lesson plan and the teachers still use the traditional learning models which is the lecture model. c) On average more than 70% of students have low minimum completeness criteria. d) Attitudes and behaviors of the students in the school show the lack of achievement of basic competencies to be achieved. In addition to the facts mentioned above, the unsuccessful learning model applied by the teachers at Karanganyar Wikarya Vocational School in maintaining a conducive atmosphere during the learning process makes the students feel bored and not concerned with the importance of the lesson. Then, it results in failure to achieve the expected basic competencies. Keywords : learning model, teacher, basic competence